Stock Clustering Framework using Financial Ratios: A Case Study in the Stock Exchange of Thailand - Jearanaitanakij, Kietikul; Poonpon, Natdanai; Wongtep, Chanidapa; Buriyameathakul, Kittaporn; Pimsupaporn, Artitaya (My University, 2025)
Value investors typically seek undervalued stocks that align with specific financial criteria to maximize their margin of safety. However, manually analyzing the financial data of all listed stocks is a time-intensive process. Furthermore, the market price of a target stock may exceed its intrinsic value, introducing potential investment risks. To address these challenges, this study proposes a stock clustering framework that groups equities based on financial ratio similarity. The proposed framework is designed to streamline the investment decision-making process by recommending stocks with comparable financial profiles as alternatives to those currently attracting investor interest but that may already be overvalued. Multiple clustering algorithms are evaluated to determine the most effective grouping strategy. Empirical back testing using four years of data from the Stock Exchange of Thailand reveals that the Gaussian Mixture Model (GMM) achieves the highest composite performance metric among the tested methods. Additionally, the HDBSCAN algorithm is employed to detect and exclude outlier stocks, thereby enhancing the reliability of the clustering results.
Keywords: Composite index; Financial ratios; Investment; Stock clustering; Stock exchange of Thailand